Design and Implementation of a Virtual University Network Using the Hot Standby Router Protocol - Ramah, Abdulsalam; Nuredin Ahmed, (AlQalam Journal of Medical and Applied Sciences, 2025)
With the increasing reliance on campus networks to support educational activities, the need for solutions that ensure the availability and continuity of operation has become critical. Traditional networks face the challenge of service outages when the primary virtual gateway fails, resulting in user connectivity disruptions and impacting operational reliability. Hot Standby Routing Protocol (HSRP), a first-generation hopping routing protocol, provides an effective mechanism to mitigate these failures by establishing a shared virtual gateway across multiple routers. This study aimed to design and implement a virtual campus network using HSRP and test its performance in a Cisco Packet Tracer environment. A model was built with two primary routers, four switches, and multiple endpoints, with Preemption and Interface Tracking enabled to ensure seamless transitions during failures. The model was tested in a Packet Tracer environment using various scenarios, including primary router failure, backup router failure, network interface failure, and link failure. Performance was evaluated based on convergence time, latency, packet loss, and throughput. The results showed that HSRP automatically restores service within a few seconds with minimal packet loss and a temporary spike in latency. The results confirm the effectiveness of the protocol in enhancing reliability, noting that the study is limited by simulation and a small dataset.